Reconocimiento, aplicación y exigibilidad de los derechos de la naturaleza. - Morejón, José Ignacio (2012)
This dissertation develops issues regarding recognition, implementation and enforcement of the rights of nature. The recognition of these rights is achieved through a chronological analysis of environmental law and environmental and ecological movements: the rights of nature are not the product of chance but of an evolutionary process of law and environmental movements, political and social, that have cemented the floor upon they were built. Nature is now subject of rights, and therefore, its definition as well as the definition of its rights is vital for the proper enforcement and implementation of the rights of nature thesis. The Constitution understood nature as the place where life is reproduced and performed. This place is holder of the rights of existence, maintenance, regeneration and restoration. Similarly we see that the rights of nature or Pacha Mama are interrelated and complex concepts that require an intellectual and technical development. Therefore, the correct application of the rights of nature depends on the understanding of its origins and the development its rights. Additionally it is important to rethink the law as we understand it. We need to rethink its methods, its processes and its logic, to avoid confusion with other similar but not equal rights. The dynamics of legal science must thrive on other sciences, and it is thus regenerated to meet the current needs of this generation and more to come. The biocentrism elements present in these rights requires a break up with traditional mechanisms, and pushes the development and introduction of new tools and criteria to be taken into account in a more creative legal reasoning.